Advances in multifunctional glycosylated nanomaterials: preparation and applications in glycoscience. (20th March 2015) - Adak, Avijit K.; Li, Ben-Yuan; Lin, Chun-Cheng
Graphical abstract: Highlights: Multivalent glycosylated nanoparticles can confer significantly increased functional affinity. Nanoparticles can accommodate multiple copies of different carbohydrate ligands and provide greater surface contact area. Several metallic glyconanoparticle-based high-affinity ligands have been described. Abstract: Applications of glycosylated nanomaterials have gained considerable attention in recent years due to their unique structural properties and compatibility in biological systems. In this review, glyco-nanoparticles (glyco-NPs) are defined as compounds that contain a nano-sized metallic core, are composed of noble metals, magnetic elements, or binary inorganic nanoparticles, and that exhibit carbohydrate ligands on the surface in three dimensional polyvalent displays similar to the glycocalyx structures on cell membranes. Nanomaterials decorated with suitable biological recognition ligands have yielded novel hybrid nanobiomaterials with synergistic functions, especially in biomedical applications. This review focuses on strategies for building various types of glyco-NPs and highlights their potential in targeted drug delivery and molecular imaging as well as their uses in bioassays and biosensors. The most recent examples of glyco-NPs as vaccine candidates and probes for assaying enzymes with bond-forming activities are also discussed.